Kebutuhan Cooperative Scripts Berbasis PowerPoint Untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Irwan Febryan; Ni Putu Juni Artini; Nyoman Ayu Putri Lestari; I Made Aditya Dharma (Mimbar Ilmu, 2022)
One of the causes of the lack of student interest and student activity in participating in learning is that learning is still teacher-centered and the teacher has not used many variations of models and media during learning activities, so students are easily bored. The passive participation of students in the learning process can affect student learning outcomes, such as the results of observations that have been carried out showing that many student test scores are still below the KKM. The low learning outcomes need to find a solution, namely by applying a cooperative script model assisted by PowerPoint media. The purpose of this study was to analyze the effect of the cooperative script model with the help of PowerPoint media on student learning outcomes. This study used a posttest only control group design. Data were collected by the test method. The data collection instrument was in the form of a student learning outcome test in the form of an objective test. After that the data obtained were analyzed using descriptive statistical analysis and inferential statistical analysis through t-test. The results showed that there was an effect of the cooperative script model with the help of PowerPoint media on student learning outcomes. So, it can be concluded that the cooperative script model assisted by PowerPoint media has a significant effect on student learning outcomes.